Optimization of Cash Flow and Financing Costs in Construction Projects - Ayman Abdelrahman Mostafa Hussein, Sara (AUC Knowledge Fountain, 2021)
The contractor’s cash shortage during the progress of a construction project leads to delays, penalties and may lead to project failure. Since the net difference between the cash inflow and cash outflow during construction shall be financed by the contractor, the contractor must consider methods to improve their cash flow in order to maximize the profit margin and minimize the financing costs. Several studies have covered optimization of cash flow and optimization of financing costs, separately. This model integrates both approaches in an attempt to determine the best project schedule and financing alternative; that cover the cash shortage with maximum profitability. The model proposes different ways that attempt to overcome the deficit in cash flow; first by minimizing the amount of financing required through shifting the activities with lag to enhance the cash flow, without extending the project duration, then evaluating different financing alternatives; namely long and short-term loans. The outcome of the model is a modified cash flow for the project with less financing required from the contractor, and feasible schedules of financing inflow and outflow based on the best financing alternative, that attempts to cover the lack of cash with the minimum financing cost. In addition, the model provides the user with a negotiable bid alternative that determines the optimum increase in advance payment, that shall overcome the cash shortage, without borrowing funds. The model has been tested and validated on a case study, and a sensitivity analysis has been performed.